Effect of alternating current and nitrate reducing bacteria on corrosion of X80 pipeline steel in Shenyang soil solution. (November 2021) - Fu, Qi; Xu, Jin; Wei, Boxin; Qin, Qingyu; Gao, Liqun; Bai, Yunlong; Yu, Changkun; Sun, Cheng
Graphical abstract: Highlights: The corrosion of X80 pipeline steel by alternating current (AC) and nitrate reducing bacteria (NRB) is studied. Either AC or NRB lead to pitting corrosion of X80 steel. The cooperation of AC and NRB results in larger and deeper pits on the steel surface. In the AC environment containing NRB, the samples have the deepest pitting pits and the highest corrosion rate. Abstract: In this work, electrochemical measurements and surface analysis techniques were used to investigate the effects of alternating current (AC) and nitrate reducing bacteria (NRB) on the corrosion behavior of X80 pipeline steel in the Shenyang soil extract solution. Either AC or NRB increases the corrosion rate of X80 steel samples, and the combination of AC and NRB can make the corrosion rate reach about 16.5 times of that without AC and NRB. Confocal laser scanning microscopy (CLSM) images show that the maximum pitting depth is up to 38.3 μm through the synergistic effect of AC and NRB. The data in this paper strongly confirms that AC and NRB synergistically accelerate the pitting formation of X80 pipeline steel, and lead to the generation of deeper and larger pits.